2014
DOI: 10.1016/j.pscychresns.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Opposite brain emotion-regulation patterns in identity states of dissociative identity disorder: A PET study and neurobiological model

Abstract: Imaging studies in posttraumatic stress disorder (PTSD) have shown differing neural network patterns between hypo-aroused/dissociative and hyper-aroused subtypes. Since dissociative identity disorder (DID) involves different emotional states, this study tests whether DID fits aspects of the differing brain-activation patterns in PTSD. While brain activation was monitored using positron emission tomography, DID individuals (n=11) and matched DID-simulating healthy controls (n=16) underwent an autobiographic scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 47 publications
(91 reference statements)
3
63
1
1
Order By: Relevance
“…Studies using a variety of traumatized populations demonstrate that trauma-based dissociation is associated with a state of hypo-arousal during which some regions of the brain (e.g., the prefrontal cortex) overregulate regions associated with awareness and intensity of emotions and sensations . Consistent with these patterns, Reinders et al (2003Reinders et al ( , 2006Reinders et al ( , 2014 have found differences in cortical blood flow and cardiovascular response when trauma scripts are read to individuals with dissociative identity disorder (DID) while in emotionally neutral (i.e., ANP) versus traumatized (i.e., EP) states, suggesting emotional under-and over-arousal, respectively. Professional actors attempting to simulate DID could not replicate the patterns of brain activation or heart rate variability (HRV) found in DID (Reinders et al, 2006(Reinders et al, , 2012(Reinders et al, , 2014.…”
Section: Trauma and Attachment Models Of Dissociationmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies using a variety of traumatized populations demonstrate that trauma-based dissociation is associated with a state of hypo-arousal during which some regions of the brain (e.g., the prefrontal cortex) overregulate regions associated with awareness and intensity of emotions and sensations . Consistent with these patterns, Reinders et al (2003Reinders et al ( , 2006Reinders et al ( , 2014 have found differences in cortical blood flow and cardiovascular response when trauma scripts are read to individuals with dissociative identity disorder (DID) while in emotionally neutral (i.e., ANP) versus traumatized (i.e., EP) states, suggesting emotional under-and over-arousal, respectively. Professional actors attempting to simulate DID could not replicate the patterns of brain activation or heart rate variability (HRV) found in DID (Reinders et al, 2006(Reinders et al, , 2012(Reinders et al, , 2014.…”
Section: Trauma and Attachment Models Of Dissociationmentioning
confidence: 79%
“…(, , ) have found differences in cortical blood flow and cardiovascular response when trauma scripts are read to individuals with dissociative identity disorder (DID) while in emotionally neutral (i.e., ANP) versus traumatized (i.e., EP) states, suggesting emotional under‐ and over‐arousal, respectively. Professional actors attempting to simulate DID could not replicate the patterns of brain activation or heart rate variability (HRV) found in DID (Reinders et al., , , ). HRV has also been shown to be significantly different for those with a DD (93% of whom were classified as unresolved/disorganized by the AAI) compared with matched controls.…”
Section: Trauma and Attachment Models Of Dissociationmentioning
confidence: 99%
“…The integration of heightened negative states and the decreased ability to experience positive emotions into these diagnostic guidelines highlights an emerging focus on emotion regulatory capacities in PTSD [Friedman et al, 2011;Lanius et al, 2011Lanius et al, , 2015Nawijn et al, 2015;Powers et al, 2015a,b;Resick et al, 2008;Sadeh et al, 2015;Taylor, 2015;van Wingen et al, 2011]. These opposing states have been linked to the experience of heightened or depressed emotionality, including re-experiencing symptoms and a detachment from emotional experience that occurs during emotional numbing and states of depersonalization and derealization, respectively [Etkin and Wager, 2007;Lanius et al, 2010;Nicholson et al, 2015;Reinders et al, 2014;Wolf et al, 2014]. These opposing states have been linked to the experience of heightened or depressed emotionality, including re-experiencing symptoms and a detachment from emotional experience that occurs during emotional numbing and states of depersonalization and derealization, respectively [Etkin and Wager, 2007;Lanius et al, 2010;Nicholson et al, 2015;Reinders et al, 2014;Wolf et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…As studies in PTSD have suggested not only lower HRV in PTSD but also alterations in top-down modulatory processes on a neuronal level [Etkin and Wager, 2007;Lanius et al, 2010;Nicholson et al, 2015;Reinders et al, 2014;Wolf et al, 2014], combining resting HRV and neural activation will facilitate a greater understanding of altered emotion regulatory processes in this disorder. As studies in PTSD have suggested not only lower HRV in PTSD but also alterations in top-down modulatory processes on a neuronal level [Etkin and Wager, 2007;Lanius et al, 2010;Nicholson et al, 2015;Reinders et al, 2014;Wolf et al, 2014], combining resting HRV and neural activation will facilitate a greater understanding of altered emotion regulatory processes in this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that (1) patients with DID and co-morbid PTSD and patients with PTSD only would show GM reductions compared to controls, in the frontal cortices (including anterior cingulate, medial and lateral prefrontal, orbitofrontal, superior, middle and inferior frontal) (Geuze et al, 2008;Woodward et al, 2009;Nardo et al, 2013) and insular cortex (Kasai et al, 2008) as well as in the hippocampus and amygdala (Vermetten et al, 2006;Ehling et al, 2008); (2) Differences in GM abnormalities between the two patient groups were expected in the inferior parietal cortex (Simeon et al, 2000;Reinders et al, 2003Reinders et al, , 2006Reinders et al, , 2012Reinders et al, , 2014 and the dorsal striatum . Finally, (3) we expected that volume of the GM regions sensitive to the effects of stress, such as the hippocampus, would show negative correlations with severity of the lifetime traumatizing events.…”
Section: Introductionmentioning
confidence: 99%